PEMAKNAAN MASYARAKAT TERHADAP MITOS BRAYUT DALAM KONTEKS KEKINIAN DI DESA SINGAPADU KALER, KABUPATEN GIANYAR, BALI - Widiastiti, Anak Agung Istri Putera (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The Men Brayut myth is one of the myths that developed in Balinese society. The myth of Men Brayut is interesting to study because it is able to build suggestions to society in relation to having children. In general, the tendency of the Men Brayut myth is manifested in the form of a statue of a woman and only her children, however, in Singapadu Kaler Village, there is also a statue of a man surrounded by his children and the surrounding community is said to be a statue of Pan Brayut. This is the main attraction for the author to conduct a deeper study of the myth of Men Brayut in Singapadu Kaler Village with a focus on the meaning of society in relation to the contemporary context. Analysis of the problem uses Mythology Theory, Power and Knowledge Theory, Deconstruction Theory and Semiotic Theory. The research method applied is a qualitative method. Data were collected through observation techniques, interviews and documentation studies, then analyzed descriptively qualitatively and interpretively starting with data reduction, data presentation and drawing conclusions. The results of the research show that the meaning that emerges is an indicator that the myth of Men Brayut is a reflection for the next generation to understand the existence of oral tradition as social control in society. This was intended so that the oral tradition, especially the myth of Men Brayut, as one of the cultural heritages, would not become extinct due to the strong currents of modernization. The existence of the Men Brayut myth in Singapadu Kaler Village in the contemporary context is also one of the potentials that can be developed as a tourist attraction that can become a source of community income through the packaging of myths in handicrafts as an implementation of the development of the creative economy sector.